2019
DOI: 10.1111/ajt.15346
|View full text |Cite
|
Sign up to set email alerts
|

Late intra-patient tacrolimus trough level variability as a major problem in kidney transplantation: A Collaborative Transplant Study Report

Abstract: Abbreviations: CI, confidence interval; CTS, Collaborative Transplant Study; DSA, donorspecific HLA antibodies; HR, hazard ratio; IPV, intra-patient variability.Intra-patient variability (IPV) of tacrolimus trough level has been associated with poor outcome after kidney transplantation. These findings were derived from singlecenter analyses and restricted mainly to measurements early after transplantation.We analyzed in a multicenter effort whether high IPV of tacrolimus levels at posttransplant years 1, 2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 18 publications
5
43
0
Order By: Relevance
“…48 In the current study tacrolimus coefficient of variation was a significant independent correlate of any Banff Borderline or greater TCMR (P = .018) after adjusting for other covariates confirming previous work and extending it to Banff Borderline TCMR. 48,[50][51][52][53] Younger recipient age has been correlated with the risk of TCMR, dnDSA, and ABMR in the past independent of donor age and nonadherence. [16][17]54,55 Age-dependent metabolic and immunosuppressive effects of tacrolimus have been demonstrated in murine and human CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…48 In the current study tacrolimus coefficient of variation was a significant independent correlate of any Banff Borderline or greater TCMR (P = .018) after adjusting for other covariates confirming previous work and extending it to Banff Borderline TCMR. 48,[50][51][52][53] Younger recipient age has been correlated with the risk of TCMR, dnDSA, and ABMR in the past independent of donor age and nonadherence. [16][17]54,55 Age-dependent metabolic and immunosuppressive effects of tacrolimus have been demonstrated in murine and human CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using a better statistical framework, Sapir Pichhadze et al also demonstrated that a higher standard deviation in tacrolimus levels resulted in a higher hazard ratio for a composite endpoint that included late allograft rejection, transplant glomerulopathy or total graft loss [29]. Several other studies have confirmed that a high IPV is associated with poor long-term outcomes after kidney transplantation, late allograft rejection, and reduced renal allograft survival [30][31][32][33]. In a recent study by Sablik et al it was shown that a high tacrolimus IPV was not associated with the incidence of chronic active ABMR.…”
Section: Introductionmentioning
confidence: 99%
“…High IPV in tacrolimus trough levels has been linked to adverse transplant outcomes, and is a significant risk factor for poor long‐term graft survival in pediatric solid organ transplant patients . A study of more than 6600 kidney transplant patients with a functioning graft at least 3 years post‐transplantation also showed that graft survival was significantly reduced with higher IPV . Impact of IPV on graft survival was particularly strong in adolescents 12‐17 years of age.…”
Section: Introductionmentioning
confidence: 99%